Crystal structure of 3-(4-methylphenyl)-1-phenyl-5-[(E)-2-phenylethenyl]-1Hpyrazole - Adam, Farook; Charishma, Sharath Poojary; Prabhu, Basrur Ramya; Samshuddin, Seranthimata; Ameram, Nadiah (International Union of Crystallography, 2015)
In the title compound, C24H20N2, the dihedral angles between the pyrazole ring and the pendant phenyl, toluoyl and phenylethenyl rings are 41.50 (8), 4.41 (8) and 31.07 (8), respectively. In the crystal, inversion dimers linked by a – stacking interactions between the phenylethenyl rings are observed [centroid–centroid separation = 3.5857 (9) A ° ].